Aktuelle Reformvorschläge zum Einkommensteuertarif; Current reform proposals for the German personal income tax schedule: Relieve the middle class and high earners, burden high incomes - Stefan Bach (Wirtschaftsdienst, 2021)
Der aktuelle Einkommensteuertarif belastet Mittelschichten und Besserverdienende relativ stark durch den schnellen Anstieg der Progression. Entlastungen durch eine Anhebung des Grundfreibetrags oder eine Abmagerung des Mittelstandsbauchs führen leicht zu Steuerausfällen von höheren zweistelligen Milliardenbeträgen im Jahr. Erhöhungen der Spitzensteuersätze wirken dem entgegen, allerdings sind die Aufkommenspotenziale bei den Hochverdienenden begrenzt. Sollen zum Beispiel die unteren 95 % der Bevölkerung um 1 % ihres steuerpflichtigen Einkommens entlastet werden, muss man die obersten 5 % mit knapp 3 % belasten, die Grenzbelastungen müssen um 5,5 Prozentpunkte steigen. – – The current German personal income tax schedule imposes a relatively heavy burden on the middle class due to the rapid rise in tax progression. Relief through an increase in the basic tax-free allowance or a flattening of the steep increase in marginal tax rates can easily lead to tax losses upwards of double-digit billions per year. Top tax rates reduce these losses, but the revenue potential from high earners is limited. For example, if the bottom 95 % of the population is to be relieved of 1 % of their taxable income, the top 5 % have to be charged almost 3 %, the marginal tax rate must increase by 5.5 percentage points.
Keywords: H24; H22; D31; 330; Einkommensteuertarif; Reform; Deutschland